Revisión sistemática sobre la animación a la lectura como estrategia pedagógica en estudiantes de secundaria (Memorias Sifored - Encuentros Educación UAN, 2023)
The article presents an overview of the role played by families in the reading motivation of students and its incidence in school contexts or other learning scenarios. The objective of this systematic review is to identify the importance of family support in strengthening reading skills in elementary school students. Through a documentary review with a systematic design, a search was carried out in specialized databases and 18 research studies were selected through inclusion and exclusion criteria. The results obtained compile the pedagogical strategies implemented to encourage students and their families to read in order to guarantee significant progress in academic achievement. From the studies analyzed, it was concluded that the participants have implemented various strategies that have contributed significantly to the strengthening of reading skills. Therefore, it is necessary to continue deepening in the design of specialized material and the exploration of physical, technological and audiovisual resources that contribute to continue fostering the reading habit in this population.
Keywords: Educational inclusion; reading habits; parent-school relationship; educational environment.